The information propagation mechanism of individual heterogeneous adoption behavior under the heterogeneous network - Cui, Shiru; Zhu, Xuzhen (Frontiers in Physics, 2024)
To explore heterogeneous behavior diffusion in the same population under a heterogeneous network, this study establishes a dual-layer heterogeneous network model to simulate the spreading patterns of hesitant individuals and regular individuals in different networks. It analyzes the influence of"To investigate heterogeneous behavior diffusion within the same population in a heterogeneous network, this paper establishes a dual-layer heterogeneous network model to simulate the spreading patterns of hesitant individuals and regular individuals in different networks. It analyzes the influence of individuals' hesitation states and different spreading patterns in heterogeneous networks on the information diffusion mechanism. In the propagation of this model, when either layer of the dual-layer network becomes the dominant spreading layer, second-order continuous spreading is observed. However, when the regular adoption behavior serves as the dominant spreading layer, its spreading threshold occurs earlier than the spreading threshold when hesitant adoption behavior is the dominant spreading layer. When there is no dominant spreading layer, first-order discontinuous spreading is observed, and the spreading threshold occurs later than the threshold in the presence of a dominant spreading layer.Additionally, the study discovers the existence of cross-phase transitions during the spreading process. The results of theoretical analysis align with the simulation results.